Specific PCR‐based detection of Phomopsis vexans the cause of leaf blight and fruit rot pathogen of Solanum melongena L. (1st November 2019) - Udayashankar, A.C.; Chandra Nayaka, S.; Archana, B.; Lakshmeesha, T.R.; Niranjana, S.R.; Lund, O.S.; Prakash, H.S.
Abstract: Leaf blight and fruit rot disease caused by Phomopsis vexans is a devastating disease of brinjal. The detection of P. vexans in plant parts and seeds of brinjal can be complicated, mainly when the inoculum is present at low levels and/or overgrown by fast‐growing saprophytic fungi or other seed‐borne fungi. A PCR‐based diagnostic method was developed with specific primers designed based on sequence data of a region consisting of the 5·8S RNA gene and internal transcribed spacers, ITS 1 and ITS 2 of nuclear ribosomal RNA gene (rDNA) repeats of P. vexans . The efficiency and specificity of primer pairs PvexF/PvexR designed were established by PCR analysis of DNA from P. vexans strains isolated from India and fungal isolates of other genera. A single amplification product of 323‐bp was detected from DNA of P. vexans isolates. No cross‐reaction was observed with any of the other isolates tested. The specific primers designed and employed in PCR detected P. vexans up to 10 pg from DNA isolated from pure culture. This is the first report on the development of species‐specific PCR assay for identification and detection of P. vexans . Thus, PCR‐based assay developed is very specific, rapid, confirmatory and sensitive tool for the detection of pathogen P. vexans at early stages. Significance and Impact of the Study: Phomopsis vexans is an important seed‐borne pathogenic fungus responsible for leaf blight and fruit rot in brinjal. Current detection methods, based on culture and morphological identification is time consuming, laborious and are not always reliable. A PCR‐based diagnostic method was developed with species‐specific primers designed based on sequence data of a region consisting of the 5·8S RNA gene and internal transcribed spacers, ITS 1 and ITS 2 of nuclear ribosomal RNA gene (rDNA) repeats of P. vexans .